Influence Of Heating Rate On Microstructure Of Galvannealed Coating During Hot Stamping - Henrique Lacerda Eleutério; Aldo Henrique de Almeida Barbosa; Vicente Tadeu Lopes Buono (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
The automotive industry’s interest in galvannealed (GA) boron steel for hot forming processes application has been steadily increasing due to its excellent surface quality, galvanic protection provided to the parts, good paint adhesion and better weldability in relation to other coatings for this application. In this study, samples of 22MnB5 galvannealed steel were heat treated and hot stamped on a water cooled die in laboratory scale. The influence of heat treatment on stability of coating and steel was assessed by using initial heating rates 11.0ºC/s and 15.0ºC/s. Microstructural evolution of galvannealed coating and structural integrity of steel during hot forming were investigated by scanning electron microscopy with energy dispersive spectroscopy analysis (SEM/EDS/Line scan), X-ray diffraction (XRD) and optical microscopy (OM). It was possible to quantify the Fe-Zn phase evolution during hot forming, to understand the effect of these heating rates on the product properties and to establish an optimized heat treatment for hot forming of these steel. The heat treatment with the heating rate of 15.0ºC/s presented greater operational flexibility and final products free from surface defects or cracks in the substrate.